Pengaruh kerjasama tim terhadap kepuasan kerja yang berdampak pada kinerja Pegawai UPT SDA Bah Bolon Dinas Sumber Daya Air Cipta Karya dan Tata Ruang Provinsi Sumatera Utara - Nana Triapnita Nainggolan; Darwin Lie; Lora Ekana Nainggolan (Universitas Darussalam Gontor, 2020)
UPT SDA Bah Bolon, Dinas Sumber Daya Air, Cipta Karya Dan Tata Ruang Provinsi Sumatera Utara realizes the community's need for the availability of irrigation services through enhancement, development, maintenance, preservation of irrigation networks, and optimization of the functions of irrigation building facilities. It is expected that employees will be able to work optimally in line with the increase in population and economic growth. This study aimed to know how far the influence of teamwork towards work satisfaction and their effect on employee work performance. There were 96 government employees involved in this study and it was conducted in UPT Bah Bolon. The study showed that teamwork affects the job satisfaction of employees. Another result in the study showed that teamwork did affect the employee performance, and job satisfaction of employees affect the employee work performance.